Hadis dalam Perspektif Sunni dan Syiah Imamiyah - Abdurrahman, M. (TAJDID, 2017)
By comparing the various classical and modern literatures on hadith in Sunni and Shi’i outlook, this paper examines the differences of Sunni and Shiite epistemology in viewing, valuing and utilizing hadith as the second source of Islamic teachings after the Qur’an. Although there is an epistemological difference between Sunni and Shiite in understanding the hadith, both have similar perspectives in using hadith as one of the main sources of Islamic teachings.